Molecular architecture with carbohydrate functionalized β-peptides adopting 314-helical conformation - Pawar, Nitin J.; Sidhu, Navdeep S.; Sheldrick, George M.; Dhavale, Dilip D.; Diederichsen, Ulf (Beilstein Journal of Organic Chemistry, 2014)
Carbohydrate recognition is essential in cellular interactions and biological processes. It is characterized by structural diversity, multivalency and cooperative effects. To evaluate carbohydrate interaction and recognition, the structurally defined attachment of sugar units to a rigid template is highly desired. β-Peptide helices offer conformationally stable templates for the linear presentation of sugar units in defined distances. The synthesis and β-peptide incorporation of sugar-β-amino acids are described providing the saccharide units as amino acid side chain. The respective sugar-β-amino acids are accessible by Michael addition of ammonia to sugar units derivatized as α,β-unsaturated esters. Three sugar units were incorporated in β-peptide oligomers varying the sugar (glucose, galactose, xylose) and sugar protecting groups. The influence of sugar units and the configuration of sugar-β-amino acids on β-peptide secondary structure were investigated by CD spectroscopy.
Keywords: carbohydrate recognition; conformation; glycopeptide; β-peptide; sugar amino acid